PENDIDIKAN LINGKUNGAN HIDUP DAN MASA DEPAN EKOLOGI MANUSIA - Maghfur, M (IAIN Pekalongan, 2010)
The environmental crisis being faced by people is essentiallythe impact of human behavior itself. For this reason, this paper examinesthe importance of environmental education as a vehicle fortransformation of confidence, understanding, and human ecologicalbehavior. Education has a significant role in building one’s ecologicalawareness. Through the process of environmental education, one canincrease the capacity of cognition, affection and psychomotoric, whichin turn affected the outlook and pattern of human relationship withnature. Through a process of education, ecological values that aretaught by religion can be internalized to students. The main environmentaleducation starts from the family and more emphasis on informalprocesses. Interaction which is informal and emphasize the substancewill facilitate the establishment of ecological character for learners. Inthis context, environment-based education contributes to the future ofhuman ecology and sustainability